Silica Masterbatches Produced with Liquid Phase Mixing; Part III. Quasi-Static Stress-Softening. Issue 6 (3rd October 2022) - Zhong, Liang; Lin, Feifei; He, Fujin; Xie, Mingxiu; Fu, Kai; Yi, Liming; Wang, Meng-Jiao
Abstract: The stress-softening effect of rubber-like materials is a phenomenon such that the stress required to attain a given elongation is less during the second cycle of deformation. In practice, stress-softening effects are used as a quantitative measure of strain energy loss. Both rubber reinforcement by fillers and the failure properties of vulcanizates, such as ultimate strength, tearing, cracking, abrasion, and fatigue, are closely related to the processes of energy dissipation during deformation. This paper reports the results of our research on the quasi-static stress-softening effect of vulcanizates of solution-polymerized styrene butadiene rubber (SSBR)/cis-polybutadiene rubber (BR)/silica masterbatches named Eco-Visco-Elastomer composite (EVEC) produced by a continuous liquid phase mixing, taking dry-mixed silica- and carbon black-filled vulcanizates as references. With this liquid phase mixing, the silanization efficiency of EVEC was greatly improved. Compared with the conventional silica filled vulcanizates, the stress softening effect of EVEC was significantly lower at low strain and rose more rapidly with increasing strain, which could be explained by the effects of filler agglomeration and polymer-filler interaction. The less energy dissipation at low strain is mainly due to fewer filler agglomerates, whereas at high strain, for EVEC, it is attributed to more rupture of polymer crosslinks and polymer chains in the matrix with increasing extension, due to higher polymer-filler interaction resulting in less slippage of polymer chains along the filler surfaces.